THE FEATURES OF STUDENTS MOTIVATION - Andrey Petrovich Preobrazhenskiy (Science and Innovation Center Publishing House, 2019)
This paper discusses the possibilities of motivating students during their stay in educational institutions. The features of educational and extracurricular work are noted.